Penerapan Metode Waterfall Pada Aplikasi Tracer Study Berbasis Website - Alina Mei Cahyaningtyas; Riyadi Purwanto; Prih Diantono Abda’u3 (Infotekmesin, 2022)
Tracer study is a method used by several Vocational High Schools (SMK) to collect alumni data and monitor alumni progress. The problem is in monitoring the alumni who do not only stay in Cilacap but outside of the city as well. Moreover, the data collection method is still simple by only using a questionnaire form filled out when they take their diplomas. This condition is less effective because many alumni are still looking for a job, therefore it is difficult to check up on them all the time. This study aims to create a tracer study application using the waterfall method. The testing phase uses the Blackbox testing method. Based on the test results, the application can make it easier for BKK administrators to collect alumni data and help monitor the alumni progress by checking the percentage of alumni status and making it easier for alumni to fill out questionnaires. The results of the overall usability test conducted on 30 respondents resulted in the predicate "Very Good" with an average of 85.51%.